Ezekiel’s Exagoge: a typical Hellenistic tragedy? - Edmund, Stewart (Duke University, 2018)
Ezekiel’s Exagoge is a dramatic work written in Greek, perhaps in second century BC Alexandria, the plot of which covers the events narrated in Exodus 1-15. Around a quarter of the play was preserved third hand by Eusebius. Was this play a Greek tragedy and what was its relationship to those of the Attic tragedians? While acknowledging Ezekiel’s debt to Euripides, most scholars have sought to stress the differences between the Exagoge and its antecedents. Commentators routinely note that Ezekiel fails to conform to the conventions of tragic drama known and propounded by Aristotle. As such, his play is thought to be typical of the changes that are supposed to have occurred in Hellenistic theatre. We have thus tended to view this play as an early ancestor of the ‘Lesedrama’ of Seneca. In this paper, I wish to challenge these prevailing and longstanding assumptions. They are founded, I argue, on a misconceived notion of the nature of classical tragedy. I suggest that the common reconstruction of the missing scenes (which are believed to take place in Egypt) is both unparalleled in ancient literature (including post-classical and Roman drama) and unsupported by the evidence of the text. This paper proposes an alternative reconstruction which would remove many of the supposed oddities of the play. I conclude that the Exagoge was very much a Greek tragedy, despite its Biblical subject matter, and could have been understood as such by Greek audience members. Though a Jew, Ezekiel shows both a detailed knowledge of classical tragedy and an awareness of the theatrical conventions known from the fifth and fourth centuries. This should prompt us to question whether the Exagoge can be used as evidence for major changes in dramatic performance in the Hellenistic period.